Manejo conservador en una paciente con embarazo ectópico cervical en Nariño, Colombia: Reporte de caso y revisión de la literatura (2020)
Objectives: To report a case of cervical pregnancy (CP) treated successfully with a conservative approach, and to conduct a review of the literature regarding conservative medical and surgical treatment. Materials and Methods: Patient with cervical pregnancy treated pharmacologically with methotrexate (MTX) followed by dilation and curettage, with a satisfactory clinical course. A search of articles was conducted in Medline via PubMed, LILACS, SciElo and Google Scholar using the terms "cervical ectopic pregnancy," "conservative treatment," "curettage,» "methotrexate," "uterine artery embolization," "hysteroscopy." Reports and case series were selected of patients with cervical pregnancy diagnosed on ultrasound at any gestational age, subjected to conservative medical or surgical treatment. Results: A total of 22 studies were included; 95 patients with CP treated with MTX were identified, 93 of them successfully treated. The most frequent complication was bleeding in 12%; 26% required complementary surgical treatment. Increasingly, uterine artery embolization (UAE) is carried out preventatively (7 cases) before curettage or treatment with MTX. The hysteroscopy is another recent alternative (20 cases). Abdominal hysterectomy was required in two cases, one of which was a cervico-isthmic pregnancy. Conclusions: Treatment with MTX continues to be the most frequent strategy. Dilation and curettage with endocervical plugging may be an option to consider in the emergency management of EP in primary care institutions. In institutions equipped with high complexity technology, uterine artery embolization before the surgical procedure and histeroscopy are options to be considered. Considering that early diagnosis of EP is now possible, multi-center studies comparing different management options are needed for better assessment of their safety and effectiveness. © 2019 Federacion Colombiana de Asociaciones de Obstetricia y Ginecologia (FECOLSOG).